Revised taxonomy and distributions of Costa Rican moss salamanders (Caudata: Plethodontidae: Nototriton), with descriptions of new taxa - Kubicki, Brian; Reyes, Aura; Arias, Erick (Zootaxa, 2022)
The tiny moss salamanders of the genus Nototriton within Costa Rica have long been poorly known and understood. Due to their diminutive size and specialized ecology, this taxon is very rarely studied or even represented in collections, thus resulting in much confusion surrounding the actual taxonomic and distributional status of the species within the country. As a result of hundreds of hours of fieldwork, lab work, and morphological analysis and measurement, herein we provide an updated taxonomic revision of the Costa Rican members of the genus Nototriton, with the proposal of a new subgenus and four new species.